Intraprocedural arrhythmia termination as an end point for hybrid ablation in patients with long-standing persistent atrial fibrillation: a 2-year follow-up study. (23rd April 2021) - Tan, Chen; Zeng, Li-Jun; Shi, Hai-Feng; Tian, Ying; Ma, Nan; Liu, Hao; Li, Sheng-Chao; Hu, Xue-Hong; Mei, Ju; Liu, Xing-Peng
Abstract: OBJECTIVES: Hybrid catheter and surgical ablation has emerged as an effective therapy for patients with persistent atrial fibrillation (AF). The aims of this study were to evaluate the relationship between intraprocedural arrhythmia termination and the long-term outcomes of hybrid ablation in patients with long-standing persistent AF. METHODS: From May 2015 through April 2019, 50 patients with persistent AF with a mean duration of 73.3 ± 62.1 (median 54) months underwent single-step hybrid ablation. Pulmonary vein isolation, left atrial posterior wall isolation and left atrial appendage excision or closure were performed through a left-sided thoracoscopic approach. Subsequently, all patients underwent high-density endocardial mapping and electrogram-based ablation with the end point of AF termination. RESULTS: We achieved intraprocedural AF termination in 84% (42/50) patients; this end point was reached in 16 patients during surgical ablation and in 26 patients during catheter ablation. Seven patients underwent repeat catheter ablation. After a mean follow-up period of 29 ± 13 months, the freedom from atrial tachyarrhythmia of a single procedure without the use of antiarrhythmic drugs was 70% (35/50). In the Cox regression model, intraprocedural termination of AF (hazard ratio 0.205, 95% confidence interval 0.058–0.730; P  = 0.014) was the sole predictor of success. CONCLUSIONS: The 2-year outcomes of a one-stop hybrid ablation with an end point of AF termination are promising in patients with long-standing persistent AF.